Interactive notes using scaffolding technique / Nur Nabila Shuhada Badaruddin - Badaruddin, Nur Nabila Shuhada (2016)
Ministry of Educations has put history subject as one of the condition of entry to university. The lesson and learning of history subject in classroom still considered conservative traditional, non-active and fail to create interactive environment. This subject is not a favorite subject among students. Students perceived history subject as difficult and very boring because they have to memorize facts besides understanding those facts, concepts, time historical events. This project developed by using webbased platform by using Adobe Flash CS6. The major feature of this application is interactive notes and the minor features of this application is exercise and quiz. The target audience is for form 4 students. This project developed using waterfall methodology consisting of requirement, design, implementation, verification and maintenance. The types of evaluation is pre-testing and post-testing was evaluated by 10 students from SMK Danau Kota and SJK(C) Chong Hwa. The effectiveness testing which is the students give a feedback from quiz score at pre-testing and posttesting. Responses from the evaluation testing was analyzed and the result indeed proven interactive notes using scaffolding technique is an effective method to deliver the interactive notes and also enjoyable. All the objective of this application is reached. For further work in future, the many improvement and enhancement can be made to this project as this project has improving learning method for students especially in the scope and interactive content.